Kinetika Adsorpsi Total Dissolved Solid (TDS) Dari Limbah Cair Sisa Pengeboran PT. CPI Duri-Riau Pada Karbon Aktif - Ristandi, Ristandi; Azis, Yelmida; Alfarisi, Cory (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The handling of residual drilling liquid waste is one of the milestones of the upstream oil industry, one of which is PT. CPI in the Duri Area. To improve the existing process, a study is needed, one of which is by reviewing the adsorption process used in the processing. In this research, the absorption of total dissolved solids with adsorbent using activated carbon was carried out, with variations in pH (4, 7, 10), stirring speed (100 rpm, 150 rpm, 200 rpm), and types of activated carbon (granules and powders), and also adsorption kinetics tests with pseudo-first order model, pseudo-second order model, Elovich model, and intraparticle diffusion model. The results show that the type of Granular Activated Carbon (GAC) is better with the best absorption capacity of 176.5 mg / g, the speed of 100 rpm and pH 4 can increase the efficiency of TDS adsorption up to 47.07%, and the results of adsorption kinetics from residual drilling waste PT. CPI-Duri using activated carbon follows the pseudo-second kinetic order, with the equilibrium model t/Qt = 0.0045t + 0,0704.Keywords: kinetics, adsorption, activated carbon, residual drilling liquid waste, total dissolved solid (TDS)